Development Of Educational Tourism In The Context Of The Digital Economy (Eurasian Journal of Humanities and Social Sciences, 2026)
This article analyzes the development trends of educational tourism in the context of the digital economy and its significance at both national and global levels. Educational tourism is considered as an integrated sector closely linked with digital transformation processes, highlighting its role in enhancing the export of educational services, expanding international student mobility, and strengthening the country’s global reputation. The article also examines the impact of artificial intelligence, Big Data, online and hybrid learning platforms, as well as digital marketing tools on the development of educational tourism. Furthermore, international experience and practices in Uzbekistan are studied through a comparative analysis, and the sector’s strengths, weaknesses, opportunities, and threats are identified using a SWOT analysis. Based on statistical data, the growth dynamics of international student flows are analyzed, substantiating that digital transformation is a key factor in ensuring the sustainable and competitive development of educational tourism.